Agricultural waste derived silicon carbide composite nanopowders as efficient coelectrocatalysts for water splitting; Journal of Cleaner Production; Vol. 442 - Nikitin D. S. Dmitry Sergeevich; Shanenkov I. I. Ivan Igorevich; Eletsky P. M. Petr Mikhaylovich; Nassyrbayev (Nasyrbaev) A. Artur; Tabakaev R. B. Roman Borisovich; Shanenkova Yu. L. Yuliya Leonidovna; Ryskulov Dastan Nurbekovich D. N. Dastan Nurbekovich; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich; Sivkov A. A. Aleksandr Anatolyevich (2024, 2024)
Various silicon carbide nanostructures are attracting close attention due to their excellent performance and great potential, including utilization in a variety of catalytic applications. Approaches, utilizing different industrial wastes as a starting material for the synthesis of SiC nanoparticles, are especially distinguished due to their environmental friendliness. This paper demonstrates a new two-stage technique of the preparation of dispersed SiC/C nanocomposite. A highly mineralized carbonaceous residue obtained by thermal processing of agricultural waste was used as a precursor for the synthesis in a pulsed arc discharge plasma. Rice husks, oat husks and oat straw were chosen as agricultural wastes with a high content of silicon in the mineral component. Carbonaceous residues (biochars) were obtained from the selected wastes by oxidative carbonization in a reactor with a fluidized bed of a deep oxidation catalyst at 460 ◦C. High-energy (up to 20 kJ) treatment of the obtained biochars in a pulsed (up to 1 ms) arc discharge plasma jet resulted in synthesizing a nanodispersed material (particle size <50 nm) containing hexagonal silicon carbide α-SiC. The principal possibility of using the synthesized SiC-based composite as a catalyst and cocatalyst of platinum in the hydrogen evolution reaction (HER) of water splitting is shown. The most impressive results (η10 = 18–28 mV, η100 = 84–98 mV, b = 32–64 mV) comparable with standard commercial Pt/C samples were obtained by modifying the synthesized SiC-based composite with 5 % platinum. Thus, the developed approach allows us to convert the agricultural waste into useful high-tech products in the form of an electrocatalytically active material.